Hydrostatic pressure effects on a one-dimensional defective phononic crystal comprising a polymer material. (December 2020) - Mehaney, Ahmed; Elsayed, Hussein A.
Abstract: In this research, the hydrostatic pressure effects on the transmission spectra of a one-dimensional (1D) defective phononic crystal (PnC) are calculated and studied. The transmission spectra of the defective PnC are calculated based on the transfer matrix method (TMM). To measure the hydrostatic pressure efficiently, a pressure-sensitive material such as Poly (methyl methacrylate) (PMMA) is proposed as a defect layer. Thereby, the proposed PnC structure is designed from silicon (Si) and tungsten (W) according to the configuration [(Si/W) 2 PMMA (Si/W) 2 ]. The numerical results show the appearance of a localized resonant mode through the transmission spectra. A wide pressure range from 0 GPa to 10 GPa is considered on the PnC transmission spectra and the localized resonant mode as well. Remarkably, any increase in the hydrostatic pressure value resulted in the displacement of the resonant mode towards the higher frequencies with a significant increase in its intensity as well. The effect of the PMMA thickness on the number of resonant modes is studied as well. Moreover, the proposed PnC design showed high performance for hydrostatic pressure sensing represented by the high sensitivity and Q-factor values of 556, 300 Hz/GPa and 3660, respectively. We expect this design to attract the researchers' attention to hydrostatic pressure influences that may affect different PnC designs and applications. Highlights: A highly sensitive 1D defective PnC design is proposed to sense and measure hydrostatic pressure. The PnC structure from a multilayer of silicon and tungsten with PMMA as a defect layer. The proposed sensor showed high performance and quality factor versus a wide range of pressure. The PnC design has a sensitivity of the value 556, 300 Hz/GPa and Q-factor of 3660.